Fasting and refeeding differentially regulate NLRP3 inflammasome activation in human subjects - Traba, Javier; Kwarteng-Siaw, Miriam; Okoli, Tracy C.; Li, Jessica; Huffstutler, Rebecca D.; Bray, Amanda; Waclawiw, Myron A.; Han, Kim; Pelletier, Martin; Sauve, Anthony A.; Siegel, Richard M.; Sack, Michael N. (The Journal of clinical investigation, 2015)
Activation of the NLRP3 inflammasome is associated with metabolic dysfunction, and intermittent fasting has been shown to improve clinical presentation of NLRP3 inflammasome-linked diseases. As mitochondrial perturbations, which function as a damage-associated molecular pattern, exacerbate NLRP3 inflammasome activation, we investigated whether fasting blunts inflammasome activation via sirtuin-mediated augmentation of mitochondrial integrity. We performed a clinical study of 19 healthy volunteers. Each subject underwent a 24-hour fast and then was fed a fixed-calorie meal. Blood was drawn during the fasted and fed states and analyzed for NRLP3 inflammasome activation. We enrolled an additional group of 8 healthy volunteers to assess the effects of the sirtuin activator, nicotinamide riboside, on NLRP3 inflammasome activation. In the fasting/refeeding study, individuals showed less NLRP3 inflammasome activation in the fasted state compared with that in refed conditions. In a human macrophage line, depletion of the mitochondrial-enriched sirtuin deacetylase SIRT3 increased NLRP3 inflammasome activation in association with excessive mitochondrial ROS production. Furthermore, genetic and pharmacologic SIRT3 activation blunted NLRP3 activity in parallel with enhanced mitochondrial function in cultured cells and in leukocytes extracted from healthy volunteers and from refed individuals but not in those collected during fasting. Together, our data indicate that nutrient levels regulate the NLRP3 inflammasome, in part through SIRT3-mediated mitochondrial homeostatic control. Moreover, these results suggest that deacetylase-dependent inflammasome attenuation may be amenable to targeting in human disease. ClinicalTrials.gov NCT02122575 and NCT00442195. Division of Intramural Research, NHLBI of the NIH.